The Efficacy of Local Plants in Enhancing Breast Milk Production: A Literature Review - Yayah Rokayah; Siti Rusyanti; Nani Yuningsih (Proceeding of Banten Internasional Conference on Health Advancement and Research, 2026)
Lactation insufficiency remains a common problem among breastfeeding mothers and often leads to early cessation of exclusive breastfeeding. Although synthetic galactagogues such as metoclopramide are available, their side effects have prompted growing interest in natural alternatives derived from local plants. This literature review aimed to evaluate the efficacy and safety of local plants traditionally used as galactagogues to enhance breast milk production. A total of 34 scientific articles published between 2018 and 2023 were reviewed from several international databases. The studies identified various local plants, including Moringa oleifera, Sauropus androgynus, Vigna radiata, and Glycine max, that contain bioactive compounds such as flavonoids, alkaloids, and phytoestrogens capable of stimulating prolactin secretion and supporting lactation. Evidence from randomized controlled trials and observational studies demonstrated that supplementation with these plants increased milk production and improved infant growth compared to control groups. However, the findings were inconsistent due to differences in plant preparation, dosage, and study design. Reported side effects were minimal and self-limiting, although further safety evaluations are necessary. In conclusion, local plants show promising potential as safe and effective galactagogues for enhancing breast milk production among lactating mothers. Nonetheless, more rigorous, large-scale clinical studies are needed to confirm their efficacy, clarify mechanisms of action, and develop standardized formulations for evidence-based application in maternal and child health care